Turner syndrome presented with tall stature due to overdosage of the gene - Go Hun Seo; Eungu Kang; Ja Hyang Cho; Beom Hee Lee; Jin-Ho Choi; Gu-Hwan Kim; Eul-Ju Seo; Han-Wook Yoo (Korean Society of Pediatric Endocrinology, 2015)
Turner syndrome is one of the most common chromosomal disorders. It is caused by numerical or structural abnormalities of the X chromosome and results in short stature and gonadal dysgenesis. The short stature arises from haploinsufficiency of the SHOX gene, whereas overdosage contributes to tall stature. This report describes the first Korean case of Turner syndrome with tall stature caused by SHOX overdosage. The patient presented with primary amenorrhea and hypergonadotropic hypogonadism at the age of 17 years. Estrogen replacement therapy was initiated at that time. She displayed tall stature from childhood, with normal growth velocity, and reached a final height of 190 cm (standard deviation score, 4.3) at the age of 30 years. Her karyotype was 46,X, psu idic(X)(q21.2), representing partial monosomy of Xq and partial trisomy of Xp. Analysis by multiplex ligation-dependent probe amplification detected a duplication at Xp22.3-Xp22.2, encompassing the PPP2R3 gene near the 5'-end of the SHOX gene through the FANCD gene at Xp22.2.